Enhancing mechanical properties and surface quality of FDM-printed ABS: A comprehensive study on cold acetone vapor treatment - Demircali, Ali Anil; Yilmaz, Durmus; Yilmaz, Abdurrahim; Keskin, Onur; Keshavarz, Meysam; Uvet, Huseyin (SPRINGER LONDON LTD, 2024)
The development of additive manufacturing (AM) technologies has significantly advanced fabrication capabilities, yet achieving optimal surface quality and mechanical properties in end-use products is challenging. The primary objective of this study is to improve specific characteristics of 3D-printed components by employing a chemical post-processing technique including acetone. This technique is specifically applied to acrylonitrile butadiene styrene (ABS) material, utilizing a customized mechanical cold-vapor system. A complete investigation was undertaken to assess the effects of treatment on many factors, such as temperature, solvent volume, and exposure duration, on the tensile strength, physical dimensions, and mass of the ABS samples. Acetone post-processing has notably improved tensile strength, influenced by treatment duration and temperature and has led to dimensional changes such as a slight length reduction and increases in width and thickness. Furthermore, the mass of the samples exhibited variability upon acetone treatment, which was shown to be dependent on both the ambient temperature and the duration of solvent exposure. The tensile strength was assessed under various conditions, showing a significant enhancement at higher temperatures and longer exposure times. These results, demonstrating smoother surfaces and a tensile strength increase of up to 20% at 65 degrees C, underscore the efficacy of our techniques in modifying the mechanical and physical properties of 3D-printed ABS components. This innovative approach provides valuable insights into the relationship between post-processing conditions and ABS properties, enriching the body of knowledge in AM technology.
Keywords: Additive manufacturing; Surface improvement; Chemical solvent; ABS; Cold vapor; ROUGHNESS; PARTS; STRENGTH; FINISH; Automation & Control Systems; Engineering